CONTRIBUTION OF FINANCIAL LITERACY TO THE USE OF SHARIA MOBILE BANKING SERVICES IN INDONESIA - Utama, Indra (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
Financial literacy is a process for the management of people's knowledge and beliefs to manage their personal finances in a planned way. Understanding the financial condition will result in proper behavior. This research aims to determine the influence of financial literacy, security level, service features, and subjective norms on the use of Sharia mobile banking services. This research is a quantitative study using primary data from the dissemination of a questionnaire online through the Google Form platform to sharia banking students and sharia economics users of sharia banking mobile banking services in DIY. The number of samples in this study was 100 respondents. The methods of analysis used are multiple linear regression analyses with data analysis techniques using data quality tests (validity testing and reliability tests), descriptive statistical tests, classical assumption tests (normality, multicholestearity, and heteroskedastisity), hypothesis tests (t test, F test and R2 coefficient of determination test). Testing using the help of SPSS 16.0 software. Based on the results of testing using SPSS 16.0 software shows that financial literacy variables, service features, and subjective norms have a positive and significant impact on the use of Sharia banking mobile banking services, while security level variables are positively and insignificant to the use of Sharia banking mobile banking services. The value of the regression coefficient in this study was 0.692 and it can be concluded that the variables of financial literacy, security levels, service features, and subjective norms contributed to the decision to use the Sharia banking mobile banking service.